INTEGRASI PENDIDIKAN MADRASAH DALAM SISTEM PENDIDIKAN NASIONAL (Studi kebijakan Pendidikan Madrasah di Indonesia) - Pratama, Yoga Anjas (Universitas Islam Negeri Raden Intan Lampung, 2019)
AbstractMadrasah education is Islamic education that is integrated with the national education system. But in its development Islamic education experiences various problems, namely: (1) Stigma of society that considers madrasa as second class education (2) Until the left behind of madrassas from other general education. therefore in this research will be studied more deeply, about madrasah education integration in the national education system which is reviewed based on the perspective of madrasa education policy in Indonesia. This research is library research conducted by way of tracing books, articles, and related documents, to then be analyzed using descriptive analysis. The results of this study are that madrasa education has been integrated with the national education system, madrasa education is not second class education that lags behind other general education, this is because (1) Madrasah education has the same rights as other general education (to get attention, assistance, equal treatment) (2) Madrasa education (MI, MTs, and MA) is equivalent to other general education, (3) Can move to other general education institutions with the same education pathways and levels, and (4) Can continue education to prestigious Islamic Higher Education, as well as other general education.Keywords: Policy, Madrasah Education, National Education SystemAbstrakPendidikan madrasah merupakan pendidikan Islam yang terintegrasi dengan sistem pendidikan nasional. Tetapi dalam perkembanganya pendidikan madrasah mengalami berbagai permasalahan, yaitu: (1) Stigma masyararakat yang menganggap madrasah sebagai pendidikan kelas dua (2) Hingga tertinggalnya madrasah dari pendidikan umum lainya. Untuk itu dalam penelitian ini akan dikaji lebih mendalam mengenai integrasi pendidikan madrasah dalam sistem pendidikan nasional yang dikaji berdasarkan perspektif kebijakan pendidikan madrasah di Indonesia. Penelitian ini merupakan penelitian kepustakaan yang dilakukan dengan cara menelusuri buku-buku, artikel, dan dokumen-dokumen terkait, untuk kemudian dianalisis dengan menggunakan analisis deskriptif. Hasil dari penelitian ini ialah bahwa pendidikan madrasah telah terintegrasi dengan sistem pendidikan nasional, pendidikan madrasah bukanlah pendidikan kelas dua yang tertinggal dari penidikan umum lainya, hal ini dikarenakan (1) Pendidikan madrasah mempunyai hak yang sama dengan pendidikan umum lainya (untuk mendapat perhatian, bantuan, dan perlakuan yang sama) (2) Pendidikan madrasah (MI, MTs, dan MA) setara/sederajat dengan pendidikan umum lainya, (3) Dapat pindah ke lembaga pendidikan umum lainya dengan jalur dan jenjang pendidikan yang sama, dan (4) Dapat melanjutkan pendidikan ke Pendidikan Tinggi Islam yang bergengsi, maupun pendidikan umum lainya.Kata kunci: Kebijakan, Pendidikan Madrasah, Sistem Pendidikan Nasional